Treatment with irbesatan may improve slit diaphragm alterations in rats with adriamycin-induced nephropathy. (9th May 2016) - Wang, Na; Wei, Ri-bao; Li, Ping; Li, Qing-ping; Yang, Xi; Yang, Yue; Huang, Meng-jie; Wang, Rui; Yin, Zhong; Lv, Yang; Chen, Xiang-mei
Objective: The study aimed to evaluate the effects of oral administration of irbesartan in adriamycin-induced nephropathy considering laboratory changes, kidney histology, and expression of proteins related to slit diaphragm and cytoskeleton of the podocyte. Methods: The animals were divided into control, model, methylprednisolone (MP), and irbesartan groups. The 24-hour urinary protein and biochemical indicators were determined, and renal pathological changes were observed. The mRNA and protein expression of nephrin, podocin, CD2-associated protein (CD2AP), and desmin in the kidney tissue were analyzed. Results: The urinary protein excretion levels in the MP and irbesartan groups were lower than those in the model group ( p <0.01). Electron microscopy showed that fusion of the glomerular foot processes of the rats in the irbesartan group was significantly reduced. The mRNA and protein expression levels of nephrin and podocin in the renal tissue in the MP and irbesartan groups were up-regulated compared with the model group ( p <0.05), whereas the mRNA and protein expression levels of CD2AP and desmin were significantly down-regulated ( p <0.01). Conclusions: For rats with adriamycin-induced nephropathy, irbesartan could significantly reduce proteinuria. As a possible mechanism, irbesartan may improve the slit diaphragm protein of the glomerular podocyte and stabilize the cytoskeleton of the podocyte.